An evaluation of the cash aid strategy by actionaid in promoting food security: the case of Ruwangwe ward 4, Nyanga district - Muzungu, Shorai Christopher (Midlands State University, 2017)
It is no longer a secret that food insecurity is a global virus. Due to shortages of nutritious and safe food millions of people have been driven into graves. Malnutrition and the rise of diseases have not spared the ones left behind. Initially food aid was seen as the best solution by the developed countries but the prevalence of conflicts in recipient countries and the nature of foreign aid threw the dream of having a food secure world into the dungeons. Governments tried but to provide agricultural subsidies to boost production to developing countries. Climate change derailed this plan and the only solution remaining is the adoption of cash aid as a panacea. It is in this study that the researcher makes an effective evaluation of the viability of cash aid in promoting food security in Zimbabwe generally. The study focuses on Ruwangwe Ward 4 found in Nyanga North under Manicaland Province. The remote area lies near the Zimbabwe-Mozambique border where the effects of climate change have led to chronic food insecurity. The researcher conducted a study to see if the problem can be solved. The success of the cash aid in this area will then be used as a model in tackling similar cases that have bedevilled Zimbabwe and the whole world in the past decades. Examples have been drawn from other countries in a bid to motivate Action Aid Organisation in carrying out this project in Ward 4. The researcher tried to make use of all professional procedures that should be adhered to in making academic research. Use of diagrams and lucid cases has been done to provide a clear understanding to anyone who is interested in consulting this study for any meaningful use.